PATOGENITAS SPODOPTERA LITURA MULTIPLE NUCLEAR POLYHEDROSIS VIRUS (SPLTMNPV) YANG DILINDUNGI EKSTRAK KENCUR (KAEMPFERIA GALANGA) TERHADAP LAMA HIDUP LARVA SPODOPTERA LITURA - Ainun, Irma Nur; Asri, Mahanani Tri; Rahayu, Yuni Sri (LenteraBio: Berkala Ilmiah Biologi, 2013)
Spodoptera litura is pest which causes leaf damage and distrub the process of photosynthesis that could result in loss of yields. This research aimed to describe the effect of adding the Kampferia galanga extract on SpltMNPV and to certain the effective concentration of Kampferia galanga extract as chemical protective material SpltMNPV of sun exposure to the length of life of S. litura larvae. The research design used was completely randomized design (CRD) with 5 treatments and 5 replications. The treatment was SpltMNPV+kaolin 1:4 which added with various concentrations of the Kampferia galanga extract 0%, 5%, 10%, 15%, and 20%. Each unit experiments used 10 S. litura larvaes. Data obtained in the form length of life of S. litura larvae were analyzed descriptively. The results showed that the treatment of SpltMNPV+kaolin 1:4 with various concentrations of Kampferia galanga extract (0%, 5%, 10%, 15%, and 20%) affected the length of life S. litura at 6 days, 6 days, 6 days, 5 days, and 5 days respectively with percentage of S. litura survive larvae at 28%, 22%, 12%, 12%, and 10% respectively. Treatment SpltMNPV + 1:4 kaolin + 15% Kampferia galanga extract was the most effective treatment in lenght of life of S. litura larvae.